Autophagy regulates steroid production by mediating cholesterol trafficking in endocrine cells. Issue 8 (3rd August 2019) - Texada, Michael J.; Malita, Alina; Rewitz, Kim
ABSTRACT: Steroid hormones are made from cholesterol and are essential for many developmental processes and disease conditions. The production of these hormones is nutrient dependent and tightly controlled by mechanisms that involve delivery of the precursor molecule cholesterol stored in lipid droplets (LDs). Recent studies have implicated macroautophagy/autophagy, a process regulated by nutrition, in the degradation of LDs and the mobilization of stored lipids. We recently identified an autophagy-dependent mechanism that regulates steroid production via effects on cholesterol trafficking. Through gain- and loss-of-function studies in Drosophila, we found that essential autophagy-related ( Atg ) genes are required in steroidogenic cells for normal steroid production. Inhibition of autophagy in these cells by knockdown of Atg genes causes strong accumulation of cholesterol in LDs and reduces steroid production, resembling effects seen in some lipid-storage disorders and steroid-dependent cancer conditions. This autophagy-dependent steroid hormone regulation (ASHR) process is regulated by the wts-yki/Warts-Yorkie tumor-suppressor pathway downstream of nutrition, coupling nutrient intake with steroid-dependent developmental growth. This mechanism potentially contributes to the development of certain cancers and lipid-storage disorders and thus may be of great therapeutic relevance.